Psychosexual development and satisfaction with timing of developmental milestones among adult survivors of childhood cancer. Issue 8 (16th May 2018) - Lehmann, Vicky; Keim, Madelaine C.; Ferrante, Amanda C.; Olshefski, Randal S.; Gerhardt, Cynthia A.
Abstract: Objective: To extend the limited research on psychosexual development among childhood cancer survivors, by not only focusing on the prevalence and age of milestone attainment, but also survivors' attitudes toward the timing of reaching such milestones. Methods: Adult survivors of childhood cancer ( N  = 90; M age  = 29.8, SD  = 5.2), recruited from a US pediatric institution, completed online surveys indicating whether they had reached 5 milestones of psychosexual development (ie, first kiss, first boy‐/girlfriend, first physical intimacy, sexual debut, first time in love), age at attainment, and perceptions about the timing (ie, right time, wished it had happened earlier, wished they had waited). Results: Almost all survivors had reached each milestone (≥90%), except for sexual debut (83.3%). Survivors reported their first kiss as the earliest milestone at age 14.6 ( N  = 82, 92%) and falling in love as the latest milestone at age 18.8 ( N  = 80; 90%). This timing did not differ by sex/cancer‐specific factors. Most survivors (~60%) felt they reached each milestone at the right time. Compared with US normative data, both male and female survivors were less likely to have experienced their sexual debut and were approximately 1.5 years older at sexual debut. Nevertheless, 59% of survivors felt that this timing was right and 31% wished they had waited longer. Conclusions: This is the first study to demonstrate that although childhood cancer survivors may delay some aspects of psychosexual development, most are satisfied with this timing. Research and clinical practice should emphasize survivors' perceptions/satisfaction toward psychosexual development rather than focusing only on normative milestone attainment.